Nanofibres: Friend or Foe? (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Nanofibers, particularly those of a carbonaceous content, have received increased interest in the past two decades due to their outstanding physico-chemical characteristics and their possibility to form and contribute towards a plethora of potentially advantageous materials for consumer, industrial and medical applications. Despite this, and together with the numerous research studies and published articles that have sought to investigate these aspects, the potential impact of CNTs is still not understood. Whether or not nanofibers may be able to provide a sophisticated alternative to conventional materials is still debatable, whilst their effects upon both environmental and human health are highly equivocal. How nanofibers are conceived can determine how they may interact with different environments, such as the human body. Understanding each key step of the synthesis and production of nanofibers to their use within potential applications is therefore essential in gaining an insight into how they may be perceived by any biological system and environment. Thus, obtaining such information will enable all scientific communities to begin to realize the potential advantages posed by nanofibers. The aim of this Special Issue therefore, was to provide a collective overview of nanofibers; 'from synthesis to application'. The Issue particularly focuses upon carbon-based nanofibers, but also highlights alternative nanofiber types. Emphasis is given holistically, with articles discussing the production routes of nanofibers, their plight during their life-cycle (origin to applied form and effects over time), as well as how nanofibers could either incite conflict, or provide aid to human and environmental health.